Air Personality Penyiar dalam Membangun Brand Awareness Radio Elgangga 100.3 FM - Suci Tri Setya; Nani Kurniasari (UNIVERSITAS KALBIS, 2022)
Broadcasters is a broadcast style created by broadcasters so that the programs they deliver have their own characteristics. Elgangga Radio's a Betawi accent as his trademark and builds Radio Elgangga's Brand Awareness as a dangdut radio. The purpose of this study was to determine how air personality is formed to build brand awareness in Radio Elgangga 100.3 FM. This study uses Ben G. Hennke's theory which states that the strategies that must be owned include Communication of Ideas, Communication of Personality, Projection of personality, Pronounciation, Voice Control. This study uses a post-positivistic paradigm with a descriptive qualitative research approach. The data collection techniques used were in-depth interviews and documentation. The results showed that the way to communicate with Elgangga Radio broadcasters was using Betawi language to build chemistry or closeness in greeting listeners. So that programs on Radio Elgangga always have loyal listeners.